2022
DOI: 10.7759/cureus.31337
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Osteochondral Autograft Transfer in the Management of Osteochondral Lesions of the Talus: A Systematic Review and Meta-Analysis

Abstract: Osteochondral lesions of the talus (OLT) are common following ankle trauma. Operative treatment is often required, with osteochondral autografting frequently performed for large or cystic lesions, or following failed primary surgery. The aim of this systematic review was to evaluate the current evidence for osteochondral autograft transfer system (OATS) in the management of OLT. A systematic search of the PubMed, EMBASE, Scopus, and Cochrane Library databases was performed based on the Preferred Reporting Item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…Cartilage replacement surgery include AOT and OAT, which are recommend for larger OLTs. Pain relieve and high rate of sports recovery were reported to demonstrated the effect of AOT [17,18]. However, donor-site morbidity might lead surgical failure and has been a major concern of AOT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage replacement surgery include AOT and OAT, which are recommend for larger OLTs. Pain relieve and high rate of sports recovery were reported to demonstrated the effect of AOT [17,18]. However, donor-site morbidity might lead surgical failure and has been a major concern of AOT.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional surgical procedures involve lesion exposure, debridement, and graft implantation, and malleolus osteotomy was always needed in treating some OLTs patients. A systematic review in 2022 showed a significant reduction in the level of clinical pain in patients after AOT [17]. In addition, a recent meta-analysis also found high rate of sports recovery in athletes after osteochondral autografts transplantation in 2021 [18].…”
Section: Cartilage Replacementmentioning
confidence: 99%
“…Smaller OLTs (<100 mm 2 or <10 mm in diameter) are treated with reparative procedures such as arthroscopic debridement, bone marrow stimulation (BMS) and augmentation with biological adjuvants such as platelet-rich plasma (PRP) or concentrated bone marrow aspirate (cBMA) [3,20,33,36]. Larger lesions (>100 mm 2 or >10 mm in diameter) entail replacement procedures, including autologous osteochondral transplantation (AOT), osteochondral allograft transplantation, autologous chondrocyte implantation and matrixinduced chondrocyte implantation [13,17,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, advancements in imaging modalities, arthroscopic techniques and biologicalbased treatment have brooded surgical indications for osteochondral lesion of the talus (OLTs) [1,5,13,16,23,25]. The outcome of OLT surgery depends on the ability to tailor a surgical solution to the lesion's size, depth and location [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%